A phase I clinical trial of human embryonic stem cell‐derived retinal pigment epithelial cells for early‐stage Stargardt macular degeneration: 5‐years' follow‐up. (4th August 2021) - Li, Shi‐Ying; Liu, Yong; Wang, Lei; Wang, Fang; Zhao, Tong‐Tao; Li, Qi‐You; Xu, Hai‐Wei; Meng, Xiao‐Hong; Hao, Jie; Zhou, Qi; Wang, Liu; Yin, Zheng‐Qin
Abstract: Objectives: To evaluate the long‐term biosafety and efficacy of transplantation of human embryonic stem cells‐derived retinal pigment epithelial (hESC‐RPE) cells in early‐stage of Stargardt macular degeneration (STGD1). Materials and methods: Seven patients participated in this prospective clinical study, where they underwent a single subretinal transplantation of 1 × 10 5 hESC‐RPE cells in one eye, whereas the fellow eye served as control. These patients were reassessed for a 60‐month follow‐up through systemic and ophthalmic examinations. Results: None of the patients experienced adverse reactions systemically or locally, except for two who had transiently high intraocular pressure post‐operation. Functional assessments demonstrated that all of the seven operated eyes had transiently increased or stable visual function 1‐4 months after transplantation. At the last follow‐up visit, two of the seven eyes showed visual function loss than the baseline; however, one of them showed a stable visual acuity when compared with the change of fellow eye. Obvious small high reflective foci in the RPE layer were displayed after the transplantation, and maintained until the last visit. Interestingly, three categories of patients who were classified based on autofluorescence, exhibited distinctive patterns of morphological and functional change. Conclusions: Subretinal transplantation of hESC‐RPE in early‐stage STGD1 is safe and tolerated in the long term. Further investigation is needed for choosing proper subjects according to the multi‐model image and function assessments. Abstract : Transplantation of human embryonic stem cells‐derived retinal pigment epithelial (hESC‐RPE) cells in the patients with early stage of STGD1 is safe and tolerated in the long term. Objective visual functions test after transplantation were mostly remained as the preoperative levels or improved transiently in some cases. Morphology test showed pigmentation in the fundus and high reflective foci in the RPE layer by OCT. Moreover, a new fundus autofluorescence classification was applied to group the subjects for stem cell transplantation and monitored the clinical outcomes.